A review on nitrogen flows and obstacles to sustainable nitrogen management within the Lake Victoria Basin, East Africa - Masso, Cargele; Gweyi-Onyango, J.; Luoga, H.P.; Yemefack, M.; Vanlauwe, Bernard (MDPI, 2024)
The Lake Victoria Basin (LVB) is located in the upper reaches of the Nile River Basin and is shared by five East-African countries. The population in the catchment is growing rapidly and the lake is facing several environmental problems. During the past few decades, numerous efforts have been made across the five countries, with the coordination of the Lake Victoria Basin Commission (LVBC) to reduce the loading of reactive nitrogen (Nr) into the lake and Lake Watershed. However, most of the measures envisaged to ensure long-term sustainable N management are not as easily adopted as planned. This paper reports on a review study on N flows and obstacles in achieving sustainable N management in the LVB, with the objectives of improving the understanding of the N cycle and examining the N management practices and policies that can help reduce the loss of Nr in the region. The scientific literature related to a range of N flows, N management obstacles, and options to overcome obstacles has been analyzed using N prospects developed at the global level for their potential applicability across the LVB. The study showed that an unbalanced use of N input is a serious threat to agricultural productivity leading to extreme soil N mining and degradation, with the majority of LVB farms operating within negative N balances and above the safe operating boundary for N in production systems. From the projections in N input as recommended by various stakeholders, there would likely be changes in both current yield and N use efficiency (NUE) values; however, most small-scale farmers will continue to experience low yields, which remains a challenge for food security in the area. These results suggest that scientists as well as those involved in decision-making and policymaking processes should formulate new targets for fertilizer increment to reduce the yield gap for sustainability, focusing on more integrated soil fertility as a package for nutrient management in cropping systems.